Organisational Culture, Change Readiness and Successful Change Implementation in Universities in Ghana - Abdul-Nasiru, I. (University of Ghana, 2014)
Universities have unique features from regular business entities. However, like any other organisation the environment in which they operate is constantly changing, and they need to change not only to survive but to compete successfully to achieve set objectives. This study examines universities and how they achieve success in change implementation, given their culture and readiness for change tendencies. A total of 528 participants made up of academic and non-teaching staff, as well as students were selected from ten (10) public and private universities in Ghana for the study. The mixed method was used for the data collection and analysis. Quantitative data gathered through questionnaires were analysed using the Pearson Product-Moment Correlation, Multivariate Analysis of Variance (MANOVA) and Multiple Regression. For the interviews, Thematic Analysis was used for the analysis. Results show that private universities have significant features of clan and adhocracy cultures compared with public universities. Furthermore, readiness for change mediated the relationship between organisational culture and successful change implementation (measured in terms of technology acceptance). However, data showed that there is no significant difference between public and private universities in terms of change implementation success. The findings were discussed and recommendations made in terms of strategies for achieving successful change implementation
Thesis (PHD) - University of Ghana, 2014
Keywords: Organisational Culture; Change Implementation; Universities; Ghana